Adaptations of the red fox (Vulpes vulpes) to urban environments in Sydney, Australia. Issue 1 (14th June 2020) - Gil-Fernández, Margarita; Harcourt, Robert; Newsome, Thomas; Towerton, Alison; Carthey, Alexandra
Abstract: With urban encroachment on wild landscapes accelerating globally, there is an urgent need to understand how wildlife is adapting to anthropogenic change. We compared the behaviour of the invasive red fox ( Vulpes vulpes ) at eight urban and eight peri-urban areas of Sydney, Australia. We observed fox behaviour around a lure and compared fox activity patterns to those of potential prey and to two domestic predators (dogs— Canis lupus familiaris and cats— Felis catus ). We assessed the influence of site type, vegetation cover, and distance from habitation on fox behaviour, and compared the temporal activity patterns of urban and peri-urban red foxes. Urban red foxes were marginally more nocturnal than those in peri-urban areas (88% activity overlap). There was greater overlap of red fox activity patterns with introduced mammalian prey in urban areas compared with peri-urban areas (90% urban vs 84% peri-urban). Red fox temporal activity overlapped 78% with cats, but only 20% with dogs, across both site types. The high degree of overlap with cats and introduced mammalian prey is most likely explained by the nocturnal behaviour of these species, while pet dogs are generally kept in yards or indoors at night. The behavioural differences we documented by urban red foxes suggest they may adapt to human modifications and presence, by being more nocturnal and/or more confident in urban areas.